Development of palm-based neopentyl glycol diester for transformer oil application - Abdul Raof, Nurliyana (2015)
Transformer oil plays an important role as electrical insulator of transformers. Mineral-based transformer oil has relatively high toxicity, low biodegradability and low fire point. The use of vegetable oils has constraints because the presence of beta-hydrogen in its structure renders it susceptibility to oxidation. The polyol esters have a unique feature that can overcome the oxidation problem faced by the vegetable oils. Hence the focus of this project is to study the potential of neopentyl glycol (NPG) diesters to be used as transformer oil. The synthesis of NPG diester was successfully optimized via transesterification of palm oil methyl ester (PME) with neopentyl glycol. The present study investigated the application of low-pressure technology as a new synthesis method which is able to shorten the reaction time. The optimum reaction conditions obtained by manual and response surface methodology (RSM) optimization were molar ratio of 2:1.3, reaction time of 1 hour, temperature at 182°C, pressure at 0.6 mbar and catalyst concentration of 1.2 wt%. The ester exhibited better properties than the commercial transformer oil especially with regards to the breakdown voltage, flash point and moisture content. The synthesized NPG diester was then formulated with anti-oxidant and pour point depressant to enhance its oxidative stability and low temperature properties. While 2,6-di-tert-butyl-p-cresol (DBPC) has proven to be useful and effective anti-oxidant for mineral oil, present studies indicate that it is not suitable to be used as additive in NPG diester, or in polyol ester as general. The pour point depressant on the other hand, has successfully increased the pour point of NPG diester from -14°C to -48°C. The laboratory thermal aging studies have also been developed to study the effect of temperature and aging time on selected properties and were compared with commercial mineral and refined, bleached and deodorized palm oil (RBDPO) at 90°C, 110°C and 130°C. It was found that aging has profound effect on the moisture content and acidity of the oil due to degradation of both oil and insulating paper. The result indicated that throughout the aging period, NPG diester exhibits low acid value and no significant changes to viscosity and breakdown voltage. The study on tensile properties of insulating paper aged in NPG diester at 130°C shows higher tensile strength than paper aged in mineral oil and RBDPO. The aging rate calculated based on tensile strength indicated that at high temperature, insulating paper degraded faster in mineral oil and RBDPO than in NPG diester. The synthesized NPG diester has high potential to be used as transformer oil.